Web page for a book vendor / Amber Jeet Singh Surjan Singh - Amber Jeet Singh , Surjan Singh (2000)
Web pages have become a common tool for communication and advertising the service and product available in a company with the increasing popularity of the Internet facility in Malaysia. In this project I created web site for Syarikat First Agency and Syarikat First Agency Sdn. Bhd. a book vendor and publisher for two different purpose. The first the web page should promote the vendor as a representation U.S and U.K. publishers dealer and distributor for the foreign and local customers. This \web will also deal in marketing and distribution of books for the South East and Far East region making Malaysia as their regional center. The second purpose of the web page is also have its own identity which will deal mainly with local customers and the government agency. It have option where the local customer or government agency will able to view listing of its customers for convincing bidding of government or local agency tenders. Both of the company will have same information and email contacts but one deal in publishing and the other as book vendor and distributor. There will be inter link between the two web where a user will be able to browse from one web to another web and also the down line of each web.